New Breast Cancer Radiotherapy Technology Confers Higher Complications and Costs Before Effectiveness Proven: A Medicare Data Analysis. (2nd March 2018) - Gold, Heather T.; Walter, Dawn; Tousimis, Eleni; Hayes, Mary Katherine
A new breast cancer treatment, brachytherapy-based accelerated partial breast radiotherapy (RT), was adopted before long-term effectiveness evidence, potentially increasing morbidity and costs compared with whole breast RT. The aim of this study was to estimate complication rates and RT-specific and 1-year costs for a cohort of female Medicare beneficiaries diagnosed with breast cancer (N = 47 969). We analyzed 2005-2007 Medicare claims using multivariable logistic regression for complications and generalized linear models (log link, gamma distribution) for costs. Overall, 11% (n = 5296) underwent brachytherapy-based RT; 9.4% had complications. Odds of any complication were higher (odds ratio [OR]: 1.62; 95% confidence interval [CI]: 1.49-1.76) for brachytherapy versus whole breast RT, similarly to seroma (OR: 2.85; 95% CI: 1.97-4.13), wound complication/infection (OR: 1.72; 95% CI: 1.52-1.95), cellulitis (OR: 1.48; 95% CI: 1.27-1.73), and necrosis (OR: 2.07; 95% CI: 1.55-2.75). Mean RT-specific and 1-year total costs for whole breast RT were $6375, and $19 917, $4886, and $4803 lower than brachytherapy ( P < .0001). Multivariable analyses indicated brachytherapy yielded 76% higher RT costs (risk ratio: 1.76; 95% CI: 1.74-1.78, P < .0001) compared with whole breast RT. Brachytherapy had higher complications and costs before long-term evidence proved its effectiveness. Policies should require treatment registries with reimbursement incentives to capture surveillance data for new technologies.